2012
DOI: 10.1002/pssb.201248431
|View full text |Cite
|
Sign up to set email alerts
|

Absence of nonlocal resistance in microstructures of PbTe quantum wells

Abstract: We report on experiments allowing to set an upper limit on the magnitude of the spin Hall effect and the conductance by edge channels in quantum wells of PbTe embedded between PbEuTe barriers. We reexamine previous data obtained for epitaxial microstructures of n-type PbSe and PbTe, in which pronounced nonlocal effects and reproducible magnetoresistance oscillations were found. Here we show that these effects are brought about by a quasi-periodic network of threading dislocations adjacent to the BaF 2 substrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Despite that ARPES data presented in Figs. 4(a)-4(d) confirm the expected n-type character of Pb 1−x Sn x Se, a positive sign of the Hall coefficient is observed, pointing out to a relatively large contribution from holes at the interface to BaF 2 , as found earlier for PbTe/BaF 2 epilayers [51]. Highfield parabolic positive MR for the field perpendicular to the film plane, shown in Figs.…”
Section: -5supporting
confidence: 83%
“…Despite that ARPES data presented in Figs. 4(a)-4(d) confirm the expected n-type character of Pb 1−x Sn x Se, a positive sign of the Hall coefficient is observed, pointing out to a relatively large contribution from holes at the interface to BaF 2 , as found earlier for PbTe/BaF 2 epilayers [51]. Highfield parabolic positive MR for the field perpendicular to the film plane, shown in Figs.…”
Section: -5supporting
confidence: 83%
“…Otherwise, a false nonlocal signal may occur, as it was recently demonstrated in Hall microstructures of PbTe. 37 Therefore, only a series of nonlocal voltage measurements, taken between consecutive contact probes distributed around the structure perimeter, confirms the edge conduction. Here we have shown that in the depletion regime, electric potential measured around the circumference of the structure is really compatible with the edge conduction picture.…”
Section: Nonlocal Resistancementioning
confidence: 93%
“…Corresponding measurements were reported by Brüne et al for HgTe microstructures and by Mihajlović et al for Au Hall bars. Kolwas et al carried out measurements in PbTe quantum wells and a similar setup was also used by Balakrishnan et al to experimentally determine the strength of spin–orbit coupling in graphene. However, reports for semiconductors are still rare.…”
Section: Detection Of Inverse Spin Hall Effect In H‐bar Shaped P‐gaasmentioning
confidence: 99%